Investigating the Unmet Need and Future of Neurorehabilitation in India: A Scoping Review - Dorcas B C Gandhi; Ivy A Sebastian; Amreen Mahmood; Pradeepa Nayak; Mridul Makkar; Dimple Dawar; Nistara S Chawla; Jeyaraj Durai Pandian (Iranian Rehabilitation Journal)
Objectives: This study explores the challenges of implementing physical rehabilitation for people with neurological diseases at in-hospital and community levels in India, summarizes the unmet needs of evidence-based physical neurorehabilitation in India, and explores the potential models/services that can enhance the delivery of physical rehabilitation for people with neurological diseases in India. Methods: Following the preferred reporting items for systematic reviews and meta-analysis guidelines, a scoping review was conducted, employing predefined criteria to identify 28 eligible studies for analysis. Meanwhile, by employing a narrative synthesis approach, the authors collated and summarized the data extracted from these studies to gain insights into the challenges and current requirements for neurorehabilitation in India. The narrative synthesis method facilitated the exploration of qualitative aspects, allowing for a comprehensive examination of the synthesized evidence. Results: Rehabilitation after a stroke was the primary focus of the majority of the 28 research. Rehabilitation (a), rehabilitation (b) supply of rehabilitation, rehabilitation (c) research on rehabilitation, and socioeconomic issues (d) were the four main headings used to explain the present difficulties and unfulfilled demands. We also suggested eight “models of care” based on proven strategies that have been tested before and might help address current deficiencies. Discussion: Neurorehabilitation in India is inadequate, with a lack of skilled professionals, poor accessibility to services and a rural-urban divide. Alternative models of rehabilitation provision, including multidisciplinary care, task-shifting, caregiver-led and self-help models, could address the unmet needs. Trials have explored home-based caregiver-led and technology-based models, but modifications and cultural specificity are needed. Stakeholders must mobilize support and advocate for rehabilitation’s role and value, with improved data collection and reporting to inform policy development. Conclusion: There is no one-size-fits-all solution to the diverse challenges and needs of neurorehabilitation delivery in India. Several alternative care models seem to have future promise, albeit unfulfilled demands. Some basic steps toward progress include raising public awareness, enhancing the skills of current experts and encouraging proactive engagement from state and federal governments and other interested parties.